Novel Use of Pectin as a Microneedle Base - KERİMOĞLU, OYA (PHARMACEUTICAL SOC JAPAN, 2015)
Hydrocolloid pectin formulation was utilized as a novel base for fabricating biodegradable micro-needle (MN) arrays. The pectin MNs were, on average, found to be 897.71 +/- 3.48 mu m in height and 234.31 +/- 2.27 mu m in base width, with an inter base spacing of 498.66 +/- 1.60 mu m, and corresponding to an aspect ratio of 3.83 +/- 0.04. Bovine serum albumin (BSA) and pectin gel interaction was found to be dependent on the loaded protein amount. By contrast, regardless of the amount of BSA incorporated, pectin MNs competed with BSA to form a complex with Cu2+ ions in a bicinchoninic acid (BCA) kit. The glass transition of the pectin MN base was found to be 145.15 +/- 12.09, with a delta Cp of 2.60 +/- 0.02Jg(-1)K(-1). Because pectin MNs are skin friendly and naturally occurring, with biodegradable and hydrocolloidal features, they are promising vehicle for the controlled release of macromolecules.
Keywords: microneedle; pectin; transdermal; drug delivery; hydrocolloid; COLONIC DRUG-DELIVERY; VAGINAL DELIVERY; SYSTEMS; RELEASE; MECHANISM; POLYMERS; CHITOSAN; PATCHES; BEADS; SKIN